Comparative study of the hydrogen isotopes yield from Ti, Zr, Ni, Pd, Pt during thermal, electric current and radiation heating; International Journal of Hydrogen Energy; Vol. 44, iss. 36 - Tyurin Yu. I. Yuri Ivanovich; Sypchenko V. S. Vladimir Sergeevich; Nikitenkov N. N. Nikolai Nikolaevich; Zhang Hongru; Chernov I. P. Ivan Petrovich (2019, 2019)
Title screen